The spatial shifts and vulnerability assessment of ecological niches under climate change scenarios at the genus level: A case study of Betula, China - Xian-Ge Hu; Jiahui Chen; Ying Yang; Man Shi; Peng Liu; Yiheng Lin; Jian-Feng Mao; Yousry A. El-Kassaby; Erpei Lin; Huahong Huang (Forest Ecosystems)
As global warming persistently alters and rapidly reshapes landscapes and habitats, conventional species distribution models relying solely on maintaining static conditions within the current climate are likely to falter, particularly at the genus level. Hence, we hypothesize that climate change will differentially affect ecological niches of the same genus species with various latitudinal positioning and local topography, and the high-latitude species may experience greater niche contraction than low-latitude species, and that mountainous regions with high elevational variability may serve as critical climate refugia. Herein, we simulate niche alterations and integrate an ensemble model (EM) strategy, taking into account species dispersal limitations factors (topography, soil, and ultraviolet), to construct a comprehensive habitat suitability (CHS) model for assessing the future vulnerability of the Betula genus, most of which are timber species in China. Our findings reveal that the niche spatial (geographic distribution) of most species (62%) within the Betula genus will undergo a gradual decline under climate change, supporting our hypothesis of latitudinal differentiation in climate vulnerability. Intriguingly, the projected high-latitude niche reduction within the genus cannot be counterbalanced by the anticipated niche expansion of closely related species in low-latitude regions, even considering the evident latitudinal gradient distribution of species. Nonetheless, the niche spatial of six Betula species in southwestern China remains stable or expands under warming scenarios, strongly supporting our secondary hypothesis about topographic buffering effects, which probably means the unique topography (i.e., the largest elevation difference) of this region may serve as a sanctuary for preserving Betula genetic diversity. Our results underscore the uncertain nature of pre-existing niche systems at the genus level under climate change, emphasizing the need for diligent resource management and conservation planning for vulnerable timber species.